Web-based exercise program for elderlies with mobility limitation using User-Centered Design (UCD) principle / Nur Farah Atikah Jamal - Jamal, Nur Farah Atikah (2015)
World nowadays are having ageing process. In Malaysia, population of elderlies has increases tremendously from time to time. Increases in age caused limitation among the elderlies. Mobility limitations are one of the limitations faced by the elderly. In Malaysia, the elderly with mobility limitation have problem to do exercise in their daily life. This is because the elderly are lack of knowledge on what exercise they can do as there is lack of places that they can go to exercise and current web-based program are using English as their delivery language. This research has used Norman’s Principle and User Centered Design Principle. While during design and development process, ADDIE methodology has been used which reflected to the objectives of this research. Few interviews session has been done in order to get feedback from the users regarding to the designed prototypes and changes has been made according to the user’s needs. After the web-based program has been fully developed usability testing has been done to see the usability of the developed web-based program. This research help to develop a web-based program on exercise program for elderly with mobility limitation.